Profil Klinikopatologi Pasien Osteosarcoma di Instalasi Patologi Anatomi RSUD Dr. Saiful Anwar Malang Periode 2018–2020 - prihantoro, teguh; Dewi, Rose; Norahmawati, Eviana (RSUD Dr. Saiful Anwar Province of East Java, 2022)
Background: Osteosarcoma is the most common primary bone malignancy. Although the primary tumor has been resected, the patient remains at high risk of metastases. The incidence and clinicopathological characteristics of osteosarcoma need to be studied. Aim: To obtain epidemiological data that can help in diagnosis and management of osteosarcoma. Methods: This research was conducted in a retrospective descriptive manner. The data obtained from medical records at the Anatomical Pathology Laboratory, RSU Dr. Saiful Anwar Malang in 2018-2020 which met the inclusion criteria and exclusion criteria. The variables studied included gender, age, location, subtype, grade, Huvos assessment. Results: There were 68 cases of osteosarcoma that met the criterias. Most of the patients were male (52.94%). The age of the patients was spread from 8 years to 79 years. With average age was 24.56 years, the median age was 16 years, and the most in the age range of 11-25 years. The most common location was the lower extremity (82.35%). The most subtype was osteosarcoma NOS (94.12%). The most cases were high grade (94.12%). From all of cases, 3 cases were huvos graded, 1 case were grade 1, and 2 cases were grade 2. Conclusion: Most Osteosarcoma patient are men, most often in the age range of 11-25 years. The most common location is in the lower extremities, the most subtype is osteosarcoma NOS, the most grade is High grade. Most of the cases were not carried out by huvos grading.